Penguatan Integritas Dan Moralitas Remaja Melalui Pendidikan Agama Kristen Di Tengah Disrupsi Budaya Digital - Ruhut Parningotan Tambunan; Theresa Dian Christi; Yonatan Alex Arifianto (STT INDONESIA MANADO, 2026)
Abstract: The disruption caused by digital culture has transformed the patterns of interaction, character development, and spiritual life of Christian adolescents, thereby presenting new challenges to their integrity and morality. The rapid flow of information, a culture of instant gratification, and a lack of ethical oversight are driving the degradation of values and the weakening of character grounded in biblical teachings. These conditions underscore the importance of Christian Religious Education as a means of character formation capable of instilling faith-based values in a contextually relevant manner in the digital age. This study aims to analyze the role of Christian Religious Education in strengthening the integrity and morality of adolescents amid digital cultural disruption. The research employs a descriptive qualitative approach based on a literature review, utilizing content analysis techniques to examine various works in theology and Christian education. The results indicate that Christian Religious Education plays a strategic role in building adolescents’ integrity, morality, and spirituality through the internalization of biblical values. Faith-based digital literacy, transformative learning, and the strengthening of faith communities are effective strategies for addressing the challenges of digital culture. It is concluded that Christian Religious Education must holistically integrate character development, spiritual growth, and digital ethics. This approach can enhance adolescents’ moral resilience against the negative influences of technology. Synergy among families, churches, and educational institutions is a crucial factor in shaping a generation that is principled, moral, and Christ-centered. Abstrak: Disrupsi budaya digital telah mengubah pola interaksi, pembentukan karakter, dan kehidupan spiritual remaja Kristen sehingga memunculkan tantangan baru terhadap integritas dan moralitas. Arus informasi yang cepat, budaya instan, serta minimnya kontrol etis mendorong terjadinya degradasi nilai dan melemahnya karakter yang berlandaskan ajaran Alkitab. Kondisi tersebut menegaskan pentingnya Pendidikan Agama Kristen sebagai sarana pembentukan karakter yang mampu menanamkan nilai iman secara kontekstual di era digital. Penelitian ini bertujuan menganalisis peran Pendidikan Agama Kristen dalam memperkuat integritas dan moralitas remaja di tengah disrupsi budaya digital. Penelitian menggunakan pendekatan kualitatif deskriptif berbasis studi pustaka dengan teknik analisis isi terhadap berbagai literatur teologi dan pendidikan Kristen. Hasil penelitian menunjukkan bahwa Pendidikan Agama Kristen berperan strategis dalam membangun integritas, moralitas, dan spiritualitas remaja melalui internalisasi nilai-nilai Alkitabiah. Literasi digital berbasis iman, pembelajaran transformatif, dan penguatan komunitas iman menjadi strategi efektif dalam menghadapi tantangan budaya digital. Disimpulkan bahwa Pendidikan Agama Kristen harus mengintegrasikan pembentukan karakter, penguatan spiritualitas, dan etika digital secara holistik. Pendekatan tersebut mampu meningkatkan ketahanan moral remaja terhadap pengaruh negatif teknologi. Sinergi antara keluarga, gereja, dan lembaga pendidikan menjadi faktor penting dalam membentuk generasi yang berintegritas, bermoral, dan berpusat pada Kristus.